2020
DOI: 10.17712/nsj.2020.1.20190077
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of epilepsy in Saudi pregnant women and possible effects of anti-epileptic drugs on pregnancy outcomes

Abstract: Objectives: To determine the prevalence of epilepsy in Saudi pregnant women and estimate the frequency of seizure types in suffering individuals using different anti-epileptic drug modalities. It also aimed to report the teratogenic effects of anti-epileptic drugs as observed in neonates. Methods: This prospective study was conducted at King Fahd University Hospital from June 2018 to Original Articles July 2019. Sixty-eight pregnant women diagnosed with epilepsy were included in this study. Seizure types and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…De los 37 estudios seleccionados para la síntesis cualitativa, uno fue publicado en 2022 9 , tres en 2021 [10][11][12] , seis en 2020 [13][14][15][16][17][18] , siete en 2019 [19][20][21][22][23][24][25] , siete en 2018 [26][27][28][29][30][31][32] , nueve en 2017 6,[33][34][35][36][37][38][39][40] y cuatro en 2016 [41][42][43][44] , proviniendo de 14 países repartidos por Asia, Europa, América del Norte y Oceanía.…”
Section: Resultsunclassified
“…De los 37 estudios seleccionados para la síntesis cualitativa, uno fue publicado en 2022 9 , tres en 2021 [10][11][12] , seis en 2020 [13][14][15][16][17][18] , siete en 2019 [19][20][21][22][23][24][25] , siete en 2018 [26][27][28][29][30][31][32] , nueve en 2017 6,[33][34][35][36][37][38][39][40] y cuatro en 2016 [41][42][43][44] , proviniendo de 14 países repartidos por Asia, Europa, América del Norte y Oceanía.…”
Section: Resultsunclassified
“…The malformation rate observed in the presented study was comparable to that reported in other studies. In a recent study in Saudi Arabia which included 68 women of epilepsy, congenital malformation was observed in 4 (5.9%) neonates ( AlSheikh, 2020 ). A study from the United Arab Emirates (UAE) that included 179 pregnancies of women with epilepsy observed 13 (7.26%) birth defects ( Alsaadi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adverse drug effects on the fetuses can occur, such as abortion, low birth weight, preterm birth, congenital malformations, delayed postnatal cognitive development and postnatal behavioral complications ( Tomson and Battino, 2012 ). The estimated prevalence of congenital malformations in children of women with epilepsy in Saudi Arabia is 2.5–5.9% ( Albunyan and Abo-Talib, 1999 , AlSheikh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the comorbidities that pose a teratogenic risk include gestational diabetes mellitus which is associated with higher risk of congenital malformation,[ 6 7 8 ] thyroid related diseases and medications[ 9 10 ] and epilepsy medications. [ 11 12 13 ] Awareness of women showed insufficient knowledge regarding the teratogenicity of gestational diabetes mellitus,[ 14 ] thyroid diseases and medications[ 15 ] and epileptic medications. [ 16 17 ] In general, medication use and safety during pregnancy is a highly debatable subject.…”
Section: Introductionmentioning
confidence: 99%